Between Religious Legitimacy and Statelessness: A Juridical-Sociological Study of Siri Marriage and Its Gender Consequences in Coastal Indonesia - Sartika Dwi Kusuma Wardhani; Fahmi Arif Zakaria; Darajatun Indra Kusuma Wijaya (Actual Insight, 2025)
This study examines the practice of unregistered marriage in Tambakrejo Village and its legal implications for women and children. Nikah siri, which is not recorded by the state, remains prevalent in this coastal area due to economic factors, cultural traditions, limited legal education, and complex administrative procedures. Using a juridical-sociological approach and a case study method, the research involved in-depth interviews with community leaders and the collection of secondary data from statutory regulations and previous studies. The findings reveal that local residents do not fully understand the legal consequences of nikah siri, leaving women without rights to alimony, inheritance, or legal protection in divorce cases. Children born from nikah siri also face administrative obstacles in obtaining birth certificates that include their father’s name, which affects access to education, healthcare, and other civil rights. The study emphasizes the need for preventive legal interventions and public legal awareness campaigns by the government to safeguard the rights of women and children, and to encourage the official registration of marriages to ensure legal certainty.